Old Man Peter - Golovnev, Ivan (Ethnographic Bureau Studio, 2008)
Verzio FF Submission This film takes us into the world of old Peter Sengepov, the last surviving Shaman of the Kazym River, who lives alone in the depths of the Siberian taiga. The region of the Khanty people is the basic source of oil in Russia: about 70 percent of all Russian oil is extracted here. The oil companies buy up huge territories in the North of Siberia. Indigenous people are compelled to leave these places, their own patrimonial territories, and so a modern civilization gradually absorbs an ancient culture.